Utilization of palm kernel cake as a renewable feedstock for fermentative hydrogen production. (August 2016) - Azman, Nadia Farhana; Abdeshahian, Peyman; Kadier, Abudukeremu; Shukor, Hafiza; Al-Shorgani, Najeeb Kaid Nasser; Hamid, Aidil Abdul; Kalil, Mohd Sahaid
Abstract: Fermentative hydrogen generation was studied using palm kernel cake (PKC) as sustainable cellulosic biomass. PKC was subjected to an acid hydrolysis approach using dilute H2 SO4 (7% v/v). PKC hydrolysate obtained was then diluted (70%) and used as a substrate for hydrogen generation. Chemical analysis showed that the main fermentable sugars in diluted PKC hydrolysate were glucose, xylose and mannose with the concentrations of 2.75 g/L, 2.60 g/L and 27.75 g/L, respectively. Hydrogen production was carried out by the cultivation of Clostridium acetobutylicum YM1 on PKC hydrolysate. The effect of incubation temperature, the initial pH of culture medium and microbial inoculum size on hydrogen production was studied using a statistical model. The analysis of the model generated showed that the initial pH value of the culture medium and inoculum size had significant effects on the hydrogen production. The study showed that the optimum conditions for the biohydrogen production were 30.57 °C temperature, pH 5.5 and 20% inoculum size. A verification experiment was performed in the optimum conditions determined. Experimental results of the verification test showed that a cumulative hydrogen volume of 1575 ml/L was generated with consuming 2.75 g/L glucose, 2.20 g/L xylose and 16.31 g/L mannose. Graphical abstract: Highlights: PKC can be used as substrate for fermentation. Clostridium acetobutylicum YM1 can be used for hydrogen production. Temperature, initial pH of culture and inoculum size can affect hydrogen generation. Optimum biohydrogen production from PKC was determined.